The validity and reliability of video assessment for the Dragon Challenge. Issue 3 (2nd September 2019) - Draper, Nick; Jusary, Rizanudin; Marshall, Helen
ABSTRACT: The detrimental effects of physical inactivity have become a major economic burden for many developed countries. Children with higher levels of motor competence appear to maintain higher levels of physical activity across their lifespan. The Dragon Challenge (DC) provides a reliable, but time-consuming assessment of motor competence. The aim of our research was to assess the potential of video to reduce the demands on DC assessors. Thirty-six video recordings of children performing the DC, 14 girls (Mean ± SD age = 10.6 ± 0.84 years) and 22 boys (Mean ± SD age = 11.55 ± 0.8 years) were taken during an otherwise standard DC assessment session. After live scoring each participant was scored by three assessors using video. Intra-rater reliability between live and video-recorded scores was excellent (ICC = 0.923; 95%, [CI] 0.850–0.961). There was a non-significant difference in live and video scores and results of a Bland–Altman plot indicated good levels of agreement. The use of video for DC performance appears to provide a valid and reliable time-saving alternative to live assessment, which could mean that the DC presents a viable motor competence assessment tool, results of which could be used to inform planning within the context of a school setting.